Antibacterial activity test of mahkota dewa leaf extract (Phaleri amacrocarpa) against bacteria Aeromonas hydrophilla by in vitro. Issue 1 (February 2020) - Sarendah, R A; Sudarno,; Kusdarwati, R
Abstract: Disease motile aeromonas septicemia (MAS) caused by the bacterium A. hydhrophilla, is a disease that can affect all species of freshwater fish in the tropics. The use of antibiotics for the treatment of bacterial diseases have long been used, but the use of antibiotics that are not controlled pathogens causing bacterial resistance. The purpose of this study to determine the effect and the optimum concentration of the mahkota dewa leaf extract against bacteria A. hydhrophilla . The treatment in this study was the addition of the mahkota dewa leaf extract and DMSO with a variant concentration of 100 mg, 140 mg, 180 mg, 220 mg, 260 mg, positive control using antibiotics chloramphenicol and negative controls using DMSO. Research of mahkota dewa leaf extracts to inhibit the growth of Aeromonas hydrhopilla . This is indicated resources by the formation of an inhibition zone at all concentrations. The formation of inhibition zone of the mahkota dewa against A. hydhrophilla leaf extract shows that the mahkota dewa leaf extract can inhibit the growth of bacteria.